Quantification of Porphyromonas gingivalis Bacteria in Final Trimester of Pregnant Women According to Their Oral Health Status - Roestamadji, Retno I.; Tedjosasongko, Udijanto; Indrastie, Nuraini; Diyatri, Indeswati; Surboyo, Meircurius D. C.; Sudarmo, Subijanto M.; Santoso, Budi; Takahashi, Nobuhiro (European Journal of General Dentistry, 2022)
Objective Pregnant women are more at risk to suffer dental infection. Untreated dental infection during pregnancy can lead to more serious problems to mothers and their children, such as premature birth and low birth weight. This study aims to analyzed the relationship between oral hygiene status (OHI-S) and the expression of Porphyromonas gingivalis in third trimester pregnant women.Materials and Methods This was an observational analytic study with a cross-sectional study design. Patients consisted of 37 final trimester pregnant women, divided into good OHI-S and fair OHI-S. The P. gingivalis expression was measured using real-time qPCR from the mucosal swab.Results The P. gingivalis expression found no differences between good OHI-s and fair OHI-S (p = 0.557).Conclusion Based on this study, although there was no significant difference in P. gingivalis expression in the final trimester based on their oral health status, oral health is considered important to be taken care of during pregnancy.
Keywords: OHI-S; qPCR; pregnant women; Porphyromonas gingivalis; human health